Philosophical and Scientific Foundations of Guidance and Counseling: A Systematic Literature Review Across Global Frameworks and Educational Contexts - Muqaffi; Dominikus David Biondi Situmorang; Hendrik Tuaputimain; M. Solehuddin (Bisma The Journal of Counseling, 2026)
Guidance and counseling services face challenges related to the fragmentation of philosophical and scientific foundations, which affects the development of theories, policies, and service practices globally. This study aims to analyze and synthesize trends in the development of guidance and counseling foundations through a systematic literature review (SLR) approach. The research data were obtained from international scientific publications indexed in Scopus and selected using the PRISMA protocol to ensure transparency and relevance of sources. Data analysis was conducted using the SPAR 4 SLR approach, thematic analysis, and matrix mapping to identify patterns of dominance among fundamental dimensions, variations in implementation, and the dynamics of transformation in guidance and counseling practices. The findings indicate that philosophical and psychological foundations are the most dominant dimensions in shaping ethical direction, scientific approaches, and operational service strategies. However, the integration of social, religious, pedagogical, technological, and juridical-formal dimensions remains necessary to develop services that are more adaptive, multicultural, and contextual. This study concludes that the development of guidance and counseling requires an integrative synthesis among fundamental dimensions to address the complexities of education and social changes in the 21st century. The implications of this study include strengthening counselor education curricula, developing multicultural competencies and digital literacy, as well as harmonizing professional standards and service innovations based on both global and local contexts.